Discriminating factors between successful and unsuccessful elite Youth Olympic female basketball teams - Koon Teck, K.; Wang, C. K. J.; Mallett, C. J. (Journal of Quantitative Analysis in Sports, 2012)
The purpose of the present study was to examine the differences in game-related statistics in discriminating successful from the unsuccessful female basketball teams that took part in the 1st Youth Olympic Games (YOG) FIBA33 games held in Singapore from 15 to 23 August 2010. A total of 70 games played by the 20 participating countries were used for data analysis. The game-related statistics analysed were: free-throws awarded, successful 2- and 3-points field goals, fouls (team and personal), assists, turnovers, steals, blocks and player's physical height. Results of the present study with reference to the structure coefficients (SC) showed that having taller players (SC=.38) with higher successful field goal percentage (2 points, SC=.45), less turnovers (SC=.51), more team assists (SC=.32), aggressive offensive style that could draw more fouls on opponents (SC=.58) and be awarded more free throws (SC=.40), were the significant key variables that discriminated successful from the unsuccessful teams. Ninety-five percent of the cases were correctly classified using discriminant analysis and in the cross-validation (leave-one-out method) the correct re-classification was 70%. The results can be used to inform coaches in player's recruitment and development process for FIBA 33 modified basketball game